Fieldwork and footnotes : studies in the history of European anthropology - Vermeulen, Han F., 1952-; Alvarez Roldán, Arturo, 1963-; European Association of Social Anthropologists (London ; New York : Routledge, 1995)
The history of anthropology has great relevance for current debates within the discipline, offering a foundation from which the professionalisation of anthropology can evolve. The authors explore key issues in the history of social and cultural anthropological approaches in Germany, Great Britain, France, The Netherlands, Sweden, Poland, Slovenia and Romania, as well as the influence of Spanish anthropologists in Mexico to provide a comprehensive overview of European anthropological traditions.
pt. 1. The origins of anthropology in Europe -- pt. 2. Contributions to European anthropology -- pt. 3. Anthropological traditions in Europe.
"European Association of Social Anthropologists."
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Anthropology -- Europe -- History; Ethnology -- Europe -- History; Anthropologie -- Europe -- Histoire; Ethnologie -- Europe -- Histoire; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Anthropology; Ethnology; Europe; Electronic books; History